Photo-enchanced defect reactions in CdS:Ag crystals - Khomenkova, L.Yu.; Markevich, I.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2002)
Two reversible photo-enhanced defect reactions proceeding under visible light illumination have been found in CdS:Ag crystals. The first process leads to the increase of crystal photosensitivity, which has been shown to be caused by creation of "sensitizing" recombination centres. The second process results in photosensitivity degradation that has been proved to be due to disappearance of shallow donors. The initial state of the crystal restores under heating in dark. Both reactions have been shown to vanish after Ag extraction from the crystal. Metastable clusters including Ag and Cd atoms are supposed to be responsible for these reactions.